2007
DOI: 10.1118/1.2818957
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo investigations of megavoltage cone‐beam CT using thick, segmented scintillating detectors for soft tissue visualization

Abstract: Megavoltage cone-beam computed tomography (MY CBCT) is a highly promising technique for providing volumetric patient position information in the radiation treatment room. Such information has the potential to greatly assist in registering the patient to the planned treatment position, helping to ensure accurate delivery of the high energy therapy beam to the tumor volume while sparing the surrounding normal tissues. Presently, CBCT systems using conventional MV active matrix flat-panel imagers (AMFPIs), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 71 publications
0
36
0
Order By: Relevance
“…Such an increase in DQE͑0͒ compared to that of conventional 2 as well as an earlier experimental prototype 13 reflects the more efficient use of the incident x-ray quanta, which should lead to better contrast-to-noise ratio and thus better soft-tissue delineation in MV CBCT images. 39 Although the present prototypes are far from optimal, it is anticipated that, through further iteration of design, fabrication, and characterization, MV CBCT systems based on high-efficiency, segmented scintillators can provide high quality images for soft-tissue delineation at clinically practical doses.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an increase in DQE͑0͒ compared to that of conventional 2 as well as an earlier experimental prototype 13 reflects the more efficient use of the incident x-ray quanta, which should lead to better contrast-to-noise ratio and thus better soft-tissue delineation in MV CBCT images. 39 Although the present prototypes are far from optimal, it is anticipated that, through further iteration of design, fabrication, and characterization, MV CBCT systems based on high-efficiency, segmented scintillators can provide high quality images for soft-tissue delineation at clinically practical doses.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33][34] A series of theoretical and empirical studies has been previously reported on 2D segmented crystalline scintillators, which consists of matrices of scintillating crystals separated by septal walls to limit the lateral spread of optical photons. 25,[35][36][37][38][39][40] Monte Carlo simulations of radiation and optical transport have suggested that EPIDs employing segmented CsI:Tl and Bi 4 Ge 3 O 12 ͑BGO͒ detectors up to 40 mm thick can offer DQE values of up to 29% and 42%, respectively. 36,38 Such significant improvement in DQE should allow acquisition of MV CBCT images with softtissue visualization at doses as low as ϳ3 cGy.…”
Section: Introductionmentioning
confidence: 99%
“…The crystals are arranged in the form of a twodimensional matrix of optically isolated elements-with each element consisting of a scintillating crystal surrounded by optically opaque septal wall material. Such segmented scintillators have been examined in numerous empirical 6,[8][9][10][11] and theoretical [12][13][14][15][16] studies of various designs with crystal thicknesses ranging up to 4 and 6 cm, respectively. The use of segmented scintillators in early prototypes has, thus far, been shown to significantly increase DQE values up to levels of ∼25%.…”
mentioning
confidence: 99%
“…As a result, the detective quantum efficiency ͑DQE͒ for conventional MV AMFPIs is only ϳ1%, 3 which is much lower than that for kilovoltage AMFPIs ͑ϳ40% to 80%͒. [4][5][6] In order to significantly improve portal imaging performance, 7 as well as reduce the dose requirement for MV CBCT imaging, [7][8][9] it is necessary to substantially increase the DQE of MV AMFPIs.…”
Section: Introductionmentioning
confidence: 99%